2005
DOI: 10.1002/bdm.481
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐making competence: External validation through an individual‐differences approach

Abstract: This study asks to what extent (a) individuals show consistent performance differences across typical behavioral decision-making tasks, and (b) how those differences correlate with plausible real-world correlates of good decision making. Seven tasks, chosen to span the domain of decision-making skills, were administered to participants in an ongoing longitudinal study providing extensive social, psychological, and behavioral measures. Performance scores on individual tasks generally showed small, positive inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
442
2
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 380 publications
(486 citation statements)
references
References 109 publications
25
442
2
6
Order By: Relevance
“…As the previous summary of the literature makes clear, these cognitive operations require working memory and executive control resources. In line with this view, previous A-DMC studies have shown that Resistance to Framing is positively related with a general composite measure of executive control in a sample of adolescents (Parker & Fischhoff, 2005) and with the updating/inhibition dimension of executive control beyond fluid intelligence . showed that the observed age-related decline in Resistance to Framing can be mediated by a correspondent decline in fluid intelligence.…”
Section: A Study On the Memory-decision Making Relationship: Aims Andsupporting
confidence: 56%
See 2 more Smart Citations
“…As the previous summary of the literature makes clear, these cognitive operations require working memory and executive control resources. In line with this view, previous A-DMC studies have shown that Resistance to Framing is positively related with a general composite measure of executive control in a sample of adolescents (Parker & Fischhoff, 2005) and with the updating/inhibition dimension of executive control beyond fluid intelligence . showed that the observed age-related decline in Resistance to Framing can be mediated by a correspondent decline in fluid intelligence.…”
Section: A Study On the Memory-decision Making Relationship: Aims Andsupporting
confidence: 56%
“…However, individual-differences studies on the Under/Overconfidence task have provided varying results, possibly due to differences in predictors and samples. Adolescents' performance on this task was positively associated with a general measure of executive functioning (Parker & Fischhoff, 2005), while this positive correlation was found only for some measures of executive functioning in young adults . Moreover, did not find a significant correlation between performance in Under/Overconfidence and age, whereas observed a significant negative correlation.…”
Section: A Study On the Memory-decision Making Relationship: Aims Andmentioning
confidence: 80%
See 1 more Smart Citation
“…Presumably this could affect the reasonableness of retirement planning. These results are consistent with prior research on decision-making competence, which includes a task that assesses individual differences in the coherence of expectations (Parker & Fischhoff, 2005;Bruine de Bruin et al, 2007).…”
Section: Cognitive Ability Testsupporting
confidence: 89%
“…As with many other personality traits, such behavior turns out to be situation dependent (e.g., someone who takes career risks may be a cautious investor or traveler). Looking at differences in decision-making competence (Parker & Fischhoff, 2005;Stanovich & West, 1998) The next section summarizes four application domains of the behavioral decision research strategy, with analogies to cancerrelated decisions. When successful, these applications not only produce better decisions but also advance the science through the interplay of applied basic and basic applied research (Baddeley, 1979).…”
Section: Behavioral Decision Researchers Must Consider Differences Inmentioning
confidence: 99%